A novel thermodynamic method and insight of heat transfer characteristics on economizer for supercritical thermal power plant. (15th January 2020) - Wang, Yanhong; Cao, Lihua; Li, Xingcan; Wang, Jiaxing; Hu, Pengfei; Li, Bo; Li, Yong
Abstract: The technology of installing economizer has been proven to be an efficient way of recovering waste heat from flue gas of coal-fired power plants. In this study, a novel theoretical model of economizer involving heat transfer characteristics and regarding the variation of physical properties for working fluid is proposed to evaluate and analyze the thermodynamic performance of economizer for supercritical unit. With such a tool, a theoretical investigation on heat transfer characteristics and exergy analysis of process with regard to economizer installed in a 660 MW supercritical unit is performed. The performance parameters on heat transfer are graphically presented. Moreover, the heat transfer performance of economizer from novel theory is compared with that obtained by traditional method, and the drawbacks of traditional model are thoroughly revealed. Investigation results show that, the temperature difference of counter-flow heat transfer is not always greater than that of forward-flow heat transfer along heating surface length, but the boundary point appears at the dimensionless length of 0.2–0.3 of economizer area, and the lower boiler load, the closer boundary point is to 0.2. The deviation between average heat transfer coefficient and local heat transfer coefficient reaches the maximum at flue gas outlet of economizer, and which varies with load and layout. Furthermore, the heat transfer area required for each 1 °C rise of water temperature and exchanged heat, influenced by the change of physical properties of heat transfer medium, show a different trend with increment in water temperature for economizer under different arrangements. The exergy efficiency presents different variation laws in process heat transfer with different layout and different loads, and such a phenomenon is obviously different from that obtained on overall heating surface. This work provides a broadly applicable approach for economizer and even other heat exchangers to formulaically revealing the veritable microcosmic principles of heat transfer characteristics. Highlights: A novel heat-transfer model reflectingphysical parameters variation is built. Characteristicsofprocess heat-transfer foreconomizerwith different conditionsare analyzed. Variation and impact mechanismofdifferent parametersis obtained. Exergy analysisofprocess heat-transfer for economizerisimplemented. Drawbacks of traditional theoretical models under different conditions isrevealed.